Azathioprine therapy in a case of pediatric multiple sclerosis that was seropositive for MOG-IgG. (April 2017) - Zhou, Yifan; Huang, Qiao; Lu, Tingting; Sun, Xiaobo; Fang, Ling; Lu, Zhengqi; Hu, Xueqiang; Kermode, Allan; Qiu, Wei
Highlights: Our case had typical onset of ADEM at initial. Interferon beta-1a was not effective, which maybe associated with MOG-IgG. AZA was effective, particularly in poor medical resource areas. Abstract: There is a lack of evidence for treatment of pediatric multiple sclerosis (PedMS). Treatment using azathioprine for PedMS has not been reported. A 10-year-old boy with multiple sclerosis who was seropositive for antibodies against myelin oligodendrocyte glycoprotein (MOG)-IgG was treated with azathioprine plus oral methylprednisolone. The patient showed clinical and magnetic resonance imaging stability, with MOG-IgG seroconversion. There were no major side effects over a 5-year period. Azathioprine may be a treatment option, particularly in poor medical resource areas, for pediatric patients with multiple sclerosis who are seropositive for MOG-IgG.